Implementation of Telemedicine through “Apoteker Keluarga Online” Application as an Effort for Rational Headache Self-Medication - Octavia, Devi Ristian; Utami, Primanitha Ria; Susanti, Irma (JURNAL INFO KESEHATAN, 2023)
People who seek self-medication for acute headaches in pharmacies are not properly diagnosed and treated. Irrational drug use has a high potential for causing medication errors. The AKO application is one of the digital counseling service apps managed by a pharmacist who has a strategic role in educating patients on self-medication behavior in telemedicine services. The objective of this study is to identify the benefits of AKO use in increasing rational self-medication behavior in headache complaints. It is a descriptive analysis study with a case-control design. The population is the Lamongan community who have had headache self-medication. Samples were taken by purposive sampling technique. A total of 130 participants were divided into two groups: the intervention group and the control group. A headache self-medication questionnaire was employed as the instrument. The collected data was then analyzed using the Mann Whitney test to determine the value of the AKO application in increasing knowledge of the rationality of self-medication in headache complaints. The data from the measurement of the level of knowledge of the rationality of headache self-medication revealed that the majority of the intervention group (92.3%) had good knowledge and none had poor knowledge. While there are still respondents with less knowledge (15.3%) in the control group. The statistical test results for the benefits of AKO application assistance on the level of knowledge of the rationality of headache self-medication revealed a p value = 0.000, indicating a significant difference between the intervention and treatment groups. The use of telemedicine via the AKO application can increase public awareness of the rational use of headache medications. Digital health services can be used as a medium for counseling and remote patient health monitoring.